The Higher the Needs, the Lower the Tolerance: Extreme Events May Select Ectotherm Recruits With Lower Metabolic Demand and Heat Sensitivity - Vajedsamiei, Jahangir; Wahl, Martin; Schmidt, Andrea Lee; Yazdanpanahan, Maryam; Pansch, Christian (Frontiers in Marine Science, 2021)
Ongoing climate warming demands a better understanding of whether or how the ectotherms that evolved in response to fluctuating stress regimes may acquire increased heat tolerance. Using blue mussels, Mytilus spp., a globally important and well-studied species, we provide empirical evidence supporting that (i) extremely warm (future) summer conditions may select rare recruits that are more capable of expressing metabolic (feeding and respiration) suppression and recovery in response to daily thermal fluctuations in mild to critical temperature range, (ii) this higher heat tolerance can be mediated by lower baseline metabolic demand, possibly decreasing the risks of heat-induced supply and demand mismatch and its associated stress during thermal fluctuations, and (iii) the capacity to acquire such heat tolerance through acclimation is minor. We discuss our results, methodological limitations and offer a perspective for future research. Further evaluation of mechanistic hypotheses such as the one tested here (based on the role of metabolic demand) is needed to generalize the significance of drivers of fast warm adaptation in ectothermic metazoan populations.